Higher-order structure of bovine mitochondrial tRNA(SerUGA): chemical modification and computer modeling. - Watanabe, Y (1994)
On the basis of enzymatic probing and phylogenetic comparison, we have previously proposed that mammalian mitochondrial tRNA(sSer) (anticodon UGA) possess a slightly altered cloverleaf structure in which only one nucleotide exists between the acceptor stem and D stem (usually two nucleotides) and the anticodon stem consists of six base pairs (usually five base pairs) [Yokogawa et al. (1991) Nucleic Acids Res. 19, 6101-6105]. To ascertain whether such tRNA(sSer) can be folded into a normal L-shaped tertiary structure, the higher-order structure of bovine mitochondrial tRNA(SerUGA) was examined by chemical probing using dimethylsulfate and diethylpyrocarbonate, and on the basis of the results a tertiary structure model was obtained by computer modeling. It was found that a one-base-pair elongation in the anticodon stem was compensated for by multiple-base deletions in the D and extra loop regions of the tRNA(SerUGA), which resulted in preservation of an L-shaped tertiary structure similar to that of conventional tRNAs. By summarizing the findings, the general structural requirements of mitochondrial tRNAs necessary for their functioning in the mitochondrial translation system are considered.